Methodology for determining the suitability of soils for afforestation in plain part of Ukraine - Raspopina , S. P. (Man and Environment. Issues of Neoecology, 2023)
Purpose. To develop a methodology for assessing forest suitability for certain varieties of unproductive soils.Methods. There are used the classical methods of soil science, agrochemistry, forest science, forest management, typology and mathematical statistics.Results. The principles of forest typology are the basis for determining the suitability of soils for forestation. Its essence lies in a comprehensive study of soil properties (soil morphometry, chemical composition) and forestry characteristics of forest stands, as well as an analysis of the grass-shrub layer by ecomorphs. The results of studies of the combined study of the productivity of forest stands and the properties of the main varieties of unproductive soils (sandy, eroded and skeletal) in different natural zones of the plain part of Ukraine are presented. Determination of the suitability of soils for forestation was assessed according to three categories: 1) unsuitable for forestation and conditionally suitable for forestation (very dry, very poor, toxic, with a limited rhizosphere zone, inaccessible or hardly accessible for cultivation); 2) limited suitability for forestation (dry and poor soils); 3) suitable for forestation. Packages of markers have been developed, on the basis of which it is possible to assess both their forest suitability and determine the type of forest growth conditions of non-forest lands. When compiling markers, preference was given to such soil indicators, which, along with informativeness in relation to soil quality, did not require complex methods of determination. The composition of markers includes morphological, physical, agrochemical parameters and depends on the type of soil.Conclusions. The developed packages of markers are the basis for the scientifically based creation of forests on unproductive lands, on which forest vegetation did not grow before. Their use in afforestation increases its efficiency and makes forests more resistant to adverse environmental factors. The Methodology is intended for forestry specialists, it can be used at enterprises, institutions of the forest sector, forest design organizations, as well as in related industries concerned with the protection and rational use of natural resources. The methodological developments can be included in the curricula of secondary and higher forestry-oriented education institutions.